Biochemical Mechanisms and Catabolic Enzymes Involved in Bacterial Estrogen Degradation Pathways. Issue 6 (22nd June 2017) - Chen, Yi-Lung; Yu, Chang-Ping; Lee, Tzong-Huei; Goh, King-Siang; Chu, Kung-Hui; Wang, Po-Hsiang; Ismail, Wael; Shih, Chao-Jen; Chiang, Yin-Ru
Summary: Estrogens have been classified as group 1 carcinogens by the World Health Organization and represent a significant concern given that they are found in surface waters worldwide, and long-term exposure to estrogen-contaminated water can disrupt sexual development in animals. To date, the estrogen catabolic enzymes and genes remain unknown. Using a tiered functional genomics approach, we identified three estrogen catabolic gene clusters in Sphingomonas sp. strain KC8. We identified several estrone-derived compounds, including 4-hydroxyestrone, a meta -cleavage product, and pyridinestrone acid. The yeast-based estrogen assay suggested that pyridinestrone acid exhibits negligible estrogenic activity. We characterized 17β-estradiol dehydrogenase and 4-hydroxyestrone 4, 5-dioxygenase, responsible for the 17-dehydrogenation and meta -cleavage of the estrogen A ring, respectively. The characteristic pyridinestrone acid was detected in estrone-spiked samples collected from two wastewater treatment plants and two suburban rivers in Taiwan. The results significantly expand our understanding of microbial degradation of aromatic steroids at molecular level. Highlights: Initial steps of estrogen catabolism were investigated in Sphingomonas sp. strain KC8 Three estrogen catabolic gene clusters were identified in its genome Enzyme responsible for the meta -cleavage of the estrogen A ring was characterized Pyridinestrone acid was detected in estrone-spiked environmental samples Abstract : Estrogens are common surface-water contaminants with endocrine-disrupting and carcinogenic activities. Tiered functional genomic analyses and biochemical studies on Sphingomonas sp. strain KC8, an estrogen-degrading bacterium, enabled the characterization of the dioxygenase-mediated 4, 5- seco pathway, along with its corresponding genes and enzymes.